2017
DOI: 10.1016/j.neo.2017.01.001
|View full text |Cite|
|
Sign up to set email alerts
|

Physical and Functional Interactions between ELL2 and RB in the Suppression of Prostate Cancer Cell Proliferation, Migration, and Invasion

Abstract: Elongation factor, RNA polymerase II, 2 (ELL2) is expressed and regulated by androgens in the prostate. ELL2 and ELL-associated factor 2 (EAF2) form a stable complex, and their orthologs in Caenorhabditis elegans appear to be functionally similar. In C. elegans, the EAF2 ortholog eaf-1 was reported to interact with the retinoblastoma (RB) pathway to control development and fertility in worms. Because RB loss is frequent in prostate cancer, ELL2 interaction with RB might be important for prostate homeostasis. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 31 publications
1
29
0
Order By: Relevance
“…The major signaling pathways altered in the mouse ELL2 knockout prostate are likely conserved and are also involved in ELL2 action in human prostate cancer cell lines. We have previously reported downregulation of ELL2 mRNA in high‐Gleason score prostate cancer specimens . The downregulation of ELL2 protein in clinical prostate cancer specimens is consistent with its mRNA downregulation.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The major signaling pathways altered in the mouse ELL2 knockout prostate are likely conserved and are also involved in ELL2 action in human prostate cancer cell lines. We have previously reported downregulation of ELL2 mRNA in high‐Gleason score prostate cancer specimens . The downregulation of ELL2 protein in clinical prostate cancer specimens is consistent with its mRNA downregulation.…”
Section: Discussionsupporting
confidence: 75%
“…Our previous studies showed that the ELL2 mRNA was downregulated in prostate cancer specimens, particularly in high Gleason grade prostate cancer specimens . ELL2 mutation is not frequent in prostate cancer .…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…ELL2 was previously identified as androgen responsive gene in the prostate cancer cell line LNCaP [17]. We also recently showed that knockdown of ELL2 in C4-2 and LNCaP cells significantly enhanced invasion and migration and induced a slight increase in BrdU incorporation (Qiu et al 2017). Here, knockdown of ELL2 in LNCaP prostate cancer cells induced an increase in cellular proliferation (Figure 3D).…”
Section: Resultsmentioning
confidence: 99%
“…Eaf2 knockout mice developed high-grade murine prostatic intraepithelial neoplasia and increased vascularity in several murine strains (mPIN) (Xiao, et al 2008; Pascal et al 2013). Recently, we reported that siRNA knockdown of ELL2 in combination with RB enhanced proliferation, migration and invasion in prostate cancer cell lines LNCaP, C4-2 and 22RV1, while ELL2 knockdown alone enhanced migration and invasion but did not induce a statistically significant increased proliferation (Qiu, et al 2017). ELL2 expression was down-regulated in high Gleason score prostate cancer specimens.…”
Section: Introductionmentioning
confidence: 99%